2004
DOI: 10.1523/jneurosci.0703-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Functional Changes of Prefrontal Cortex in Long-Term Memory: A Repetitive Transcranial Magnetic Stimulation Study

Abstract: Neuroimaging findings suggest that the lateralization of prefrontal cortex activation associated with episodic memory performance is reduced by aging. It is still a matter of debate whether this loss of asymmetry during encoding and retrieval reflects compensatory mechanisms or de-differentiation processes. We addressed this issue by the transient interference produced by repetitive transcranial magnetic stimulation (rTMS), which directly assesses causal relationships between performance and stimulated regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
135
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(145 citation statements)
references
References 52 publications
(68 reference statements)
7
135
2
1
Order By: Relevance
“…Interestingly, studies using transcranial magnetic stimulation (TMS) also have provided some support for the idea that increased bilateral PFC activation is beneficial for performance in older adults. Two studies have shown that using TMS to reduce activity in either the left PFC during encoding or the right PFC during retrieval reduces memory performance in younger adults, but has less effect in older adults, presumably because the unstimulated hemisphere can support the function when the other is inactivated 50,51 . Therefore, these studies all suggest that older adults can recruit higher levels of brain activity than young adults, often in the PFC, and that this additional activity can aid performance of the old adults who are best able to engage it.…”
Section: Compensation In the Older Brainmentioning
confidence: 99%
“…Interestingly, studies using transcranial magnetic stimulation (TMS) also have provided some support for the idea that increased bilateral PFC activation is beneficial for performance in older adults. Two studies have shown that using TMS to reduce activity in either the left PFC during encoding or the right PFC during retrieval reduces memory performance in younger adults, but has less effect in older adults, presumably because the unstimulated hemisphere can support the function when the other is inactivated 50,51 . Therefore, these studies all suggest that older adults can recruit higher levels of brain activity than young adults, often in the PFC, and that this additional activity can aid performance of the old adults who are best able to engage it.…”
Section: Compensation In the Older Brainmentioning
confidence: 99%
“…Bilateral recruitment of parietal and prefrontal cortices was primarily observed in older participants who performed better or as well as young adults on a variety of perceptual and cognitive tasks (Cabeza et al, 2002;Grady et al, 1994;Park & Reuter-Lorenz, 2009;ReuterLorenz & Cappell, 2008;Thorpe et al, 1996). Furthermore, inhibition of prefrontal activity during recognition memory tasks significantly impaired older adults' performance (Rossi et al, 2004), whereas stimulation of prefrontal activity in under-performing older adults improved memory scores (Sole-Padulles et al, 2006) suggesting an adaptive role of prefrontal recruitment in healthy aging.…”
Section: Age Differences In Multisensory Integration and Visual Dommentioning
confidence: 99%
“…Actually, in the studies that have shown the HAROLD phenomenon (2)(3)(4)(5)11), all subjects worked on the same memory tasks despite the fact that cognitive performance of older adults deteriorates, and WM is one of the most affected cognitive functions (12)(13)(14). This cognitive deterioration might make a task subjectively more demanding for older subjects, so that they need the recruitment of contralateral counterparts in prefrontal cortex to perform as well as the young subjects (14)(15)(16).…”
mentioning
confidence: 99%
“…To distinguish between these alternatives, we asked whether the activation strengths in cross-hemispheric pairs of prefrontal areas differ between hemispheres of both young and old adults when we match the subjective difficulty of WM tasks, and task demands are high. We specifically focused on dorsolateral prefrontal cortex (DLPFC) and anterior prefrontal cortex (aPFC) because these areas have been shown to be bilaterally engaged in elderly adults during memory tasks (2,11). We additionally considered ventrolateral prefrontal Significance One principle of human cerebral cortex is its lateralized functional architecture supporting processes such as language, precise motor control of the hands, and working memory.…”
mentioning
confidence: 99%